<u>Answer</u>
0
<u>Explanation</u>
(2m)/(2m+3)-(2m)/(2m-3)=1
Simplifying the left hand first
(2m)/(2m+3)-(2m)/(2m-3) = {2m(2m-3) - 2m(2m+3)}/(4m²-9)
(4m²-6m-4m²-6m)/(4m²-9)
= (-12m) / (4m²-9)
Now this equet to 1
(-12m) / (4m²-9) = 1
-12m = 4m²-9
4m²+ 12m -9 =0 ⇒⇒⇒ This is a quadratic equation that has 2 real solutions.
4m²+ 12m -9 =0
m² + 3m + (3/2)²= 9/4 + 9/4
(m + 3/2)² = 18/4
m = √18/2 - 3/2 or m = -√18/2 - 3/2
= 0.621 = -3.621
So we can say that the equation has NO extraneous solutions.
Answer = 0
Answer:
1) 4-(-6) = 10
2) -10.3-(-7.79)= -2.51
3) -4+6 1/2= 2 1/2
4) -10.2+4.38= 5.82
5)
Step-by-step explanation:
1) A double - equals positive so change to
4+6=10
2) adding positive to negative makes it less negative
3) just change positions -4 from 6 1/2
4) makes it less negative
5) sorry I hat fractions can't do it
Answer:
6561 / 128
Step-by-step explanation:
The nth term of a geometric sequence is:
a = a₁ (r)ⁿ⁻¹
The first term is 3, and the fourth term is 81/8.
81/8 = 3 (r)⁴⁻¹
27/8 = r³
r = 3/2
The eighth term is therefore:
a = 3 (3/2)⁸⁻¹
a = 6561 / 128
Answer:
The answer is 9.2 * 10^7
Step-by-step explanation:
(1.5*10^8)-(5.8*10^7)=92,000,000
92,000,000= 9.2* 10^7